A comparison of the perceived importance and performance of midwives’ roles between midwives and nurses in Korea: a cross-sectional study - Kyungwon Kim; Yunmi Kim; Jummi Park (Korean Journal of Women Health Nursing, 2023)
Purpose This study aimed to identify the perceptions, importance, and performance of midwives’ roles among midwives and nurses in Korea. Methods A descriptive correlational design was employed. Data were collected from 164 nurses and 79 midwives from April 1 to June 25, 2021. Midwives enrolled in the Korean Midwifery Association and nurses and midwives from two hospitals each Daegu and Gyeonggi Province in Korea were invited to participate. The independent t-test, chi-square test, the Welch-Aspin test, and Pearson correlation coefficient were used for analysis. Results The midwives’ role perception score (3.47±1.46) was lower than that of nurses (3.95±0.85), and the midwives’ role performance score (2.98±0.83) was also lower than that of nurses (3.34±0.89). Significant differences were observed between midwives and nurses in their perception and performance of roles related to prenatal management, childbirth management, management of psychological changes, postpartum management, and newborn care. Higher role perception and performance among midwives were linked to the management of psychological changes and women’s health, indicating potential areas for future development. Conclusion The study results suggest directions for developing new roles for midwives. It is necessary to find a way to expand the field of midwives in public health by benchmarking the roles of midwives in various countries.